PENGAPLIKASIAN CERTAINTY FACTOR PADA SISTEM PAKAR UNTUK MENDIAGNOSA PENYAKIT CAMPAK RUBELLA - Zuhriyah, Sitti; Wahyuningsih, Pujianti (ILKOM Jurnal Ilmiah, 2019)
Rubella measles is a disease that can infect to the pregnant mothers, toddlers, children, and adults. The purpose of this study is applicate the certainty factor method to the expert system application based on website to diagnose the rubella measles disease. The utilization of information technology into the expert system application can help society to detect the rubella measles disease early. Certainty factor is one method that can be used to handle a problem that is uncertain the answer. In this study, the certainty factor method has been applied on expert system application to diagnose rubella measles based on symptoms of the disease felt by patients. The result of this study is an expert system based on the website can provide information and diagnose symptoms of rubella measles following the questions proposed by the system and symptoms of the disease felt by the patient.